2007
DOI: 10.1093/intqhc/mzm025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacy validation in a computerized physician order entry context

Abstract: Pharmacy validation produced only a moderate short-term impact on the reduction of potential prescribing errors. However, pharmacy validation may also provide ongoing benefits by identifying necessary improvements in the computerized physician order entry system. Those improvements would allow pharmacists to concentrate on the most relevant interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 24 publications
0
36
0
7
Order By: Relevance
“…In the field of medical informatics, numerous experts recognize that the majority of e-Rx systems need further refining (15,38). If community pharmacists want this technology to contribute to their professionalization, they need to collaborate in this development in order to ensure that systems marketed are well-adapted to their needs and practices (39).…”
Section: The Quality Of E-rx and Prescription Executionmentioning
confidence: 99%
“…In the field of medical informatics, numerous experts recognize that the majority of e-Rx systems need further refining (15,38). If community pharmacists want this technology to contribute to their professionalization, they need to collaborate in this development in order to ensure that systems marketed are well-adapted to their needs and practices (39).…”
Section: The Quality Of E-rx and Prescription Executionmentioning
confidence: 99%
“…Previous studies have shown that while implementing CPOE can improve the safety and efficiency of order processing, it can create new challenges and resource demands that place increased burden on pharmacists, such as increasing new types of errors and problems caused by CPOE systems. [26][27][28][29] While CPOE systems can increase efficiency in many areas, such systems should be monitored by management so any new problems that arise can be addressed.…”
Section: A Particular Facet Of the Results Is That While Time Spent Onmentioning
confidence: 99%
“…patient selection in the context of a more personalized practice of medicine) [44][45][46]. In the pharmaceutical domain at HEGP, the EHR/CDW integration was found invaluable in the evaluation of the frequency of both drug prescription and drug dispensing errors [47][48], the impact of alerts on drug dosage adjustment [49], the role of pharmacy drug order validation [50], but also to automatically detect drug-drug interactions [51] or to perform in-silico evaluations of decision rules for further integration into the operational environment of the CPOE [52].…”
Section: The Use-quality Circlementioning
confidence: 99%